1. x=2y-10 from the first given equation
==> 3(2y-10)-y=0 by removing each x and putting 2y-10 in its place in the 2nd equation.
==> 5y-30=0
==> y=6
==> x=2
Similarly
2. x=2y
==> 5y=0
==>y=0
==>x=0
3. x= 1-2y
==> 5-10y-4y=-23
==> 14y=28
==> y=2
==> x=-3
2007-03-17 04:30:35
·
answer #1
·
answered by Ceaser 2
·
1⤊
0⤋
sure i will have faith it. this is how one might bypass approximately simplifying this equation. 5(-3x-2)-(x-3)= -4(4x+5)+a million (-15x-10)-x+3= (-16x-20)+a million -15x-10-x+3= -16x-20+a million -15x-x+16x= -20-3+a million+10 -16x+16x= -23+11 0 =/= -12 Yep, advantageous that it rather is -12 (neg. twelve) . a million) Multiply 5 with the help of each and every thing interior the parentheses. flow around the (=) sign and multiply -4 with the help of each and every thing in that parentheses. 2) clean the parentheses 3) this is the equation without () 4) team like numbers and warning signs (x's with x's) (numbers w/ #) 5) Simplify answer 0 isn't equivalent to a -12
2016-10-18 22:14:10
·
answer #2
·
answered by porix 4
·
0⤊
0⤋
1)x-2y=-10
3x-y=0
Subtract 3x from both sides:
-y=-3x
Divide -1 from both sides:
y=3x
x-2(3x)=-10
x-6x=-10
-5x=-10
x=2
y=3(2)
y=6
The solution set is (2,6)
Check:
2-2(6)=-10
2-12=-10
-10=-10
3(2)-6=0
6-6=0
0=0
Just apply this example to the next two problems. I hope this helps!
2007-03-17 05:03:39
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
1. x-2y= -10......(i)
3x-y=0...........(ii)
Take equation (i)
x-2y= -10
or, x= -10+2y
or, x=2y-10
Substituting the value of x in eq (ii),
3x-y=0
3(2y-10)-y=0
6y-30-y=0
5y=30
y=6
putting the value of y in eq(i),
x-2y= -10
x-2*6= -10
x-12=-10
x=-10+12
x=2
Therefore x=2 and y=6
2. x-2y= 0......(i)
3x-y=0...........(ii)
Take equation (i)
x-2y= 0
or, x= 0+2y
or, x=2y
Substituting the value of x in eq (ii),
3x-y=0
3(2y)-y=0
6y-y=0
5y=0
y=0
putting the value of y in eq(i),
x-2y= 0
x-2*0= 0
x-0=0
x=0
Therefore x=0 and y=0
3.x+2y=1......(i)
5x-4y= -23....(ii)
Take equation (i)
x+2y=1
or, x=1-2y
Substituting the value of x in eq (ii),
5x-4y= -23
or, 5(1-2y)-4y= -23
or, 5-10y-4y= -23
or, -14y=-23-5
or, -14y=-28
or, y=2
putting the value of y in eq(i),
x+2y=1
or, x+2*2=1
or, x+4=1
or, x=1-4
or, x= -3
Therefore x=-3 and y=2
2007-03-17 04:48:53
·
answer #4
·
answered by Bubblez 3
·
1⤊
0⤋